Konsep dan Teori Permintaan Uang dalam Perspektif Islam - Putri Nadhila Maulani; Rahma Oktavia; Ulfazira Afratul Islamy; Faisal Hidayat (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
The demand for money is closely related to the purchasing power of the people in a country. The purchasing power of money in a country is influenced by inflation, when there is an increase in inflation, then with it there will be a decrease in the purchasing power of the money, while when there is a decrease in inflation, the opposite will happen, namely the occurrence of greed for the purchasing power of money. The demand for money, in addition to being influenced by inflation, is also influenced by non-cash payment instruments, which are increasingly diverse in type, making a negative effect on the demand for money, because transactions with non-cash have resulted in a lack of demand for money. A lot of the money that is scattered is already available.